2061 : Odyssey three - Clarke, Arthur C. (London : HarperCollins, 1987)
Heywood Floyd, survivor of two previous encounters with the mysterious monoliths, must once again confort Dave Bowman, a newly independent HAL, and the power of an alien race.
Keywords: Science fiction